Mortuary variability and social diversity in Ancient Greece : studies on Ancient Greek death and burial - Dimakis, Nikolas; Dijkstra, Tamara M. (Archaeopress archaeology., 2020)
This volume brings together early career scholars working on funerary customs in Greece from the Early Iron Age to the Roman period. Papers present various thematic and interdisciplinary analysis in which funerary contexts provide insights on individuals, social groups and communities.